The dynamics of the urban population in Kazakhstan in modern conditions - Altayev, A (Journal of history, 2020)
The modern world in the first place is the urban structure of the population. More than half of the world’s population are city dwellers. Urbanization has long been a leading trend of world’s development, but in the presence of common features urbanization process has its own characteristics in different countries, which are expressed by the level and pace of urbanization. According to the level of urbanization it can be distinguished by following ways: highly-urbanized, medium and weakly-urbanized countries. The first group consists of countries in which the proportion of the urban population is more than 50%, the second group includes countries where the share is 20-50%, and the third group consists of countries where proportion of the urban population is less than 20%. Kazakhstan is part of a group of highly urbanized countries, the proportion of it’s urban population in 2012 was 54.7%.